Non-Muslims’ citizenship in Islamic Law: A critique from a constitutional perspective - Haneef, Sayed Sikandar Shah (The Other Press, 2015)
The question of non-Muslims citizens of the modern Muslim states as to whether they are citizens or dhimmis is one of the most contested issues in Modern literature on Islamic political system. The constitutional dimension which needs to be focused has not been taking into account in much of the writings on the issue. This paper argues for addressing the issue from constitutionalist perspective to put the issue in its proper perspective in the modern -nation-sates contexts.